2016
DOI: 10.1111/ijfs.13026
|View full text |Cite
|
Sign up to set email alerts
|

The prevention of fish spoilage by high antioxidant Australian culinary plants: Shewanella putrefaciens growth inhibition

Abstract: Summary Shewanella putrefaciens is a marine bacterium and a major microbial cause of spoilage in low temperature stored seafood. A survey of fruits and culinary herbs was undertaken on Australian plants with high antioxidant capacities. Twenty‐eight extracts from thirteen plant species were investigated for the ability to inhibit S. putrefaciens growth. Of these, eight extracts (28.6%) substantially inhibited S. putrefaciens growth. The muntries (Kunzea pomifera), lemon aspen (Acronychia acidula) and desert li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 38 publications
(45 reference statements)
0
48
1
Order By: Relevance
“…A high antioxidant capacity has been postulated as being responsible for the medicinal properties of many plants. [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] In particular, antioxidants have been linked to antibacterial, antifungal and antiviral activities, as well as anticancer properties. 26-44 . However, other studies have indicated that antioxidants may protect cells from oxidative stress and thus protect against cell death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high antioxidant capacity has been postulated as being responsible for the medicinal properties of many plants. [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] In particular, antioxidants have been linked to antibacterial, antifungal and antiviral activities, as well as anticancer properties. 26-44 . However, other studies have indicated that antioxidants may protect cells from oxidative stress and thus protect against cell death.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34] Briefly, 100 µL of each bacterial culture was grown in 10 mL of fresh nutrient broth until they reached a count of ~10 8 cells/mL. A volume of 100 µL of the bacterial suspension was spread onto nutrient agar plates and extracts were tested for antibacterial activity using 5 mm sterilised filter paper discs.…”
Section: Evaluation Of Antimicrobial Activitymentioning
confidence: 99%
“…[18][19][20] Briefly, 100 µL of each bacterial culture was grown in 10 mL of fresh nutrient broth until they reached a count of ~10 8 cells/mL. A volume of 100 µL of the bacterial suspension was spread onto nutrient agar plates and extracts were tested for antibacterial activity using 5 mm sterilised filter paper discs.…”
Section: Evaluation Of Antimicrobial Activitymentioning
confidence: 99%
“…[12][13][14] Briefly, 100 µL of each bacterial culture was grown in 10 mL of fresh nutrient broth until they reached a count of ~10 8 cells/mL. A volume of 100 µL of the bacterial suspension was spread onto nutrient agar plates and extracts were tested for antibacterial activity using 5 mm sterilised filter paper discs.…”
Section: Evaluation Of Antimicrobial Activitymentioning
confidence: 99%